KEPALA MADRASAH SEBAGAI PENDIDIK UNTUK MENINGKATKAN KOMPETENSI GURU DI MADRASAH TSANAWIYAH FADHILAH PEKANBARU - Amin, Muhammad (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2024)
This study aims to analyze the role of the madrasah head as an educator in improving teacher competence at MTs Fadhilah Pekanbaru. The method used in this research is a qualitative approach with a case study design, which involves interviews, observations, and document analysis. The results showed that the madrasah principal functions as a leader who not only manages the school but also provides direct guidance to teachers. The implemented professional development programs, such as training and workshops, proved effective in improving teachers' pedagogical competencies. In addition, madrasah principals who apply inspirational and collaborative leadership styles can increase teachers' motivation to innovate in teaching. Nevertheless, the study also identified challenges faced, such as a lack of resources and support from outside parties. Overall, madrasah principals who act as educators can significantly improve teachers' competencies, which has a positive impact on the quality of education in the madrasah. This study recommends that madrasah principals continue to develop leadership skills and strengthen professional development programs to support the improvement of teachers' competencies.